Deep-Water Benthic Polychaetes (Vigtorniella zaikai and Protodrilus sp.) in the Black Sea as Indicators of the Hydrogen Sulfide Zone Boundary - Zaika, V.E.; Sergeeva, N.G. (Вестник зоологии, 2012)
The Black Sea hypoxic layer, situated near the boundary of the hydrogen sulfide zone, is inhabited by the polychaetes Vigtorniella zaikai, Kisseleva, 1992 and Protodrilus sp., which can serve as indicators of the interface between oxic and anoxic water. The maximum number of polychaetes in the northern part of the Black Sea occur at a depth of 150 m, while near Bosporus, where the flow of the Marmara Sea water enters the Black Sea, the peak depth varies from 150 to 250 m.